Análise da Microbiota Intestinal de ratos, antes e após da retirada da Valva Ileocecal e restabelecimento do trânsito com criação de "Esfíncter Artificial" - Angela Aparecida Barra (2012)
Several techniques have been employed for the creation of artificial bowel sphincters to control the speed of intestinal transit and prevent coloileal reflux. Dual circumferential seromyotomy to replace the ileocecal valve was performed by Rena at al. in 20 patients and showed satisfactory clinical results. The purpose of this 5 experimental work is to analyze, through molecular biology, the microbial diversity in the terminal ileum and proximal colon of rats before and after resection of the ileocecal valve. Then, the reconstruction of end to end ileocolic anastomosis was conducted in one group while an artificial sphincter was added in the other group, using the technique developed by Rena. Fourteen rats were operated and samples of 10 their ileum and colon contents were collected and processed as controls. After resection of the ileocecocolic junction, transit was reconstructed by end to end ileocolic anastomosis. In seven animals, an artificial sphincter was created upstream of the anastomosis. The animals were monitored for 20 days and reoperated to allow the collection of intraluminal content of the ileum and colon and processing of new 15 samples. Deoxyribonucleic Acid (DNA) was extracted from the samples for Polymerase Chain Reaction and Gel Electrophoresis with Denaturing Gradient PCR-DGGE. The electrophoretic band patterns generated from DNA samples of total bacteria were submitted to the BIONUMERICS software system for similarity analysis using "Dice" coefficient and diversity analysis of the microbiota by Shannon-Weaver 20 Index. The dendrogram generated from the "Dice" coefficient of all samples did not establish a correlation for ileal or colonic segments and samples of the respective control animals. The values of the Shannon-Weaver index was limited to between 2.11 and 2.93, with variations for different segments in both groups. The average of the index was higher in the ileum segment (2.61) and colon (2.57) in animals with an 25 artificial sphincter and in the colon (2.63) in animals without an artificial sphincter, compared to the control sample (2.38, 2.39 and 2.36, respectively). A larger amount of samples showed higher diversity values compared with colon samples, although microbial concentration is described and considered to be greater in the colon. The absence of the ileocecal junction affected diversity changes in all segments. With the 30 creation of a new sphincter, diversity increased in both segments (ileum and colon). The observed variations can be explained by the peculiar characteristics of the distribution behavior of the microflora in the digestive tract and the effect of local and systemic factors, which requires the continuity of this study focusing on quantification and specificity of bacteria.